2008
DOI: 10.1021/la801497d
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Poly(amidoamine) Dendrimers with Survanta Lung Surfactant: The Importance of Lipid Domains

Abstract: The interaction of generation 5 (G5) and 7 (G7) poly(amidoamine) (PAMAM) dendrimers with mica-supported Survanta bilayers is studied with atomic force microscopy (AFM). In these experiments, Survanta forms distinct gel and fluid domains with differing lipid composition. Nanoscale defects are induced by the PAMAM dendrimers. The positively charged dendrimers remove lipid from the fluid domains at a significantly greater rate than for the gel domains. Dendrimer accumulation on lipid edges and terraces preceding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…5,1824 Atomic force microscopy (AFM) experiments on supported lipid bilayers have provided evidence for both free and polymer-supported pores formed by cationic nanoparticles. 4,8,13,14,16,17 Although these studies provide a framework for understanding the cell membrane-cationic polymer interactions, the supported lipid bilayers have a much simpler lipid composition than living cell membranes. They are devoid of membrane proteins, cholesterol, and glycolipids.…”
Section: Introductionmentioning
confidence: 99%
“…5,1824 Atomic force microscopy (AFM) experiments on supported lipid bilayers have provided evidence for both free and polymer-supported pores formed by cationic nanoparticles. 4,8,13,14,16,17 Although these studies provide a framework for understanding the cell membrane-cationic polymer interactions, the supported lipid bilayers have a much simpler lipid composition than living cell membranes. They are devoid of membrane proteins, cholesterol, and glycolipids.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between cell membranes and nanocarriers, such as dendrimers, is very important, because in the most cases carriers have to get across the lipid bilayer without disrupting it. Previous studies based on atomic force microscopy (AFM) [12][13][14][15][16][17] isothermal titration calorimetry (ITC), fluorescence correlated spectroscopy (FCS) [17][18], in vitro experiments [13,[19][20] and molecular dynamics simulations (MD) [14,17,[21][22][23][24] showed that cationic dendrimers disrupt lipid bilayers by forming holes on the bilayer surface and may remove lipids from it. The degree of the disruption depends on the size and charge of the dendrimer.…”
Section: Introductionmentioning
confidence: 99%
“…Upon differences in cell types, the polyions can bind to the cellular compartments and accordingly induce compartmentalization within certain areas of the membranes and inadvertently trigger various signaling paths. Furthermore, nanoscaled defects were shown to be induced by PAMAM dendrimers through removing lipid from the fluid domains at a significantly greater rate than for the gel domains (Erickson et al, 2008). This reinforces a possibility of compartmentalization of synthetic polymers within different membrane domains as well as a differential effect of polymers on functional systems in the membranes that consecutively provoke inadvertent cytoplasmic/nucleic consequences directly and indirectly via secondary messengers such as G proteins.…”
Section: Cellular Trafficking and Toxicity Of Polycationic Nanostructmentioning
confidence: 57%